Atom probe tomography of phosphorus- and boron-doped silicon nanocrystals with various compositions of silicon rich oxide. (14th September 2016) - Nomoto, Keita; Gutsch, Sebastian; Ceguerra, Anna V.; Breen, Andrew; Sugimoto, Hiroshi; Fujii, Minoru; Perez-Wurfl, Ivan; Ringer, Simon P.; Conibeer, Gavin
Abstract: Abstract : We analyze phosphorus (P)- and boron (B)-doped silicon nanocrystals (Si NCs) with various compositions of silicon-rich oxide using atom probe tomography. By creating Si iso-concentration surfaces, it is confirmed that there are two types of Si NC networks depending on the amount of excess Si. A proximity histogram shows that P prefers to locate inside the Si NCs, whereas B is more likely to reside outside the Si NCs. We discuss the difference in a preferential location between P and B by a segregation coefficient.